Design of 12.5 MHz ultrashort passively mode-locked Figure-9 holmium-doped fiber laser implemented using different reflectors - Mirza, Jawad; Atieh, Ahmad; Boynukalın, Serhat; Kanwal, Benish; Aziz, Imran; Almogren, Ahmad (Frontiers in Physics, 2026)
Special cavities like Figure-8 and Figure-9 are exploited in lasers to enable self-starting passive mode-locking using nonlinear amplifying loop mirrors (NALMs) or nonlinear optical loop mirrors (NOLMs). Their significance lies in enhanced nonlinearity and intracavity feedback, enabling stable, self-sustained mode-locked pulses suitable for ultrafast fiber lasers. In this paper, we propose the design of femtosecond pulse width passively mode-locked Holmium-doped fiber laser (HDFL) operating at 2090 nm and 12.5 MHz repetition rate based on Figure-9 (F9) cavity. The F9 cavity is implemented utilizing three different reflectors, including saturable absorber (SA), simple mirror (SM), and fiber loop mirror (FLM). The performance of the proposed laser is compared for different reflectors considering characteristics of slope efficiency (SE), pulse width, optical signal to noise ratio (OSNR), peak power, and pulse energy. SA, SM, and FLM configurations yield mode-locked pulses with SEs of 35.6%, 8%, and 8.8%, pulse widths of 357.2 fs, 294 fs, and 231 fs, OSNRs of 36.4 dB, 46 dB, and 50 dB, peak powers of 13.53 kW, 6.12 kW, and 9 kW, and pulse energies of 4.83 nJ, 2 nJ, and 2.1 nJ, respectively. The analysis reveals that the FLM-based reflector achieves the shortest pulse width and highest OSNR, while the SA-based reflector delivers the highest peak power and pulse energy, highlighting trade-offs between pulse quality and energy performance in the proposed laser design.